2015
DOI: 10.4103/0976-9668.149091
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological study and management of liver abscess in a tertiary care center

Abstract: Background:Liver abscess is a burning problem in tropical nations, with often lethal consequences and diagnostic/therapeutic challenges. We have determined etiopathology, clinical, radiological, and bacteriological characteristics of this condition and review its management strategies.Materials and Methods:During the period of the month from May 2007 to September 2009, a prospective study was performed involving 125 patients admitted to the in-patient ward of the Department of General Surgery of N.R.S Medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…(Khosravani et al, 2017) Laboratory findings obtained include leukocytosis, eosinophilia, increased erythrocyte sedimentation rate (ESR), HB <10 mg%, bilirubin >1 mg/dl, increased alkaline phosphatase, increased serum glutamic oxaloacetic transaminase, increased serum glutamic pyruvic transaminase, abnormal prothrombin time (PTT) and hypoalbuminemia. (Jha et al, 2015) In our patient, showed leukocytosis, eosinophilia, increased liver function, abnormal coagulation test and hypoalbuminemia. These results are more directed to the infection process than to malignancy.…”
Section: Discussionsupporting
confidence: 48%
“…(Khosravani et al, 2017) Laboratory findings obtained include leukocytosis, eosinophilia, increased erythrocyte sedimentation rate (ESR), HB <10 mg%, bilirubin >1 mg/dl, increased alkaline phosphatase, increased serum glutamic oxaloacetic transaminase, increased serum glutamic pyruvic transaminase, abnormal prothrombin time (PTT) and hypoalbuminemia. (Jha et al, 2015) In our patient, showed leukocytosis, eosinophilia, increased liver function, abnormal coagulation test and hypoalbuminemia. These results are more directed to the infection process than to malignancy.…”
Section: Discussionsupporting
confidence: 48%
“…In the developed countries, pyogenic abscesses are more common, while in the developing and underdeveloped regions, amebic abscesses form the majority. 1,2 Abscesses involve the right lobe in about two-third of cases, probably in accordance with the proportion of portal blood received by the right lobe. Up to a fifth of the patients may have multiple abscesses.…”
Section: Liver Abscessmentioning
confidence: 70%
“…Amebic liver abscess is commonly seen in the 3rd and 4th decades, with a striking male preponderance (M:F ratio 4-10:1). 1,4,5 Most cases either reside in or have a history of recent travel to a tropical, endemic region. The imaging findings of amebic abscess have been discussed later.…”
Section: Liver Abscessmentioning
confidence: 99%
“…There were reports of chewing betel-nut (Areca catechu) increasing the risk of liver cirrhosis and liver cancer, which may then increase the risk of liver abscess 49 . And poor economic status was associated with increasing risk of pyogenic liver abscess in an India study 50 .…”
Section: Discussionmentioning
confidence: 89%